Chimeras of Dictyostelium myosin II head and neck domains with Acanthamoeba or chicken smooth muscle myosin II tail domain have greatly increased and unregulated actin-dependent MgATPase activity - Liu, Xiong (The National Academy of Sciences, 2000)
Phosphorylation of the regulatory light chain of Dictyostelium myosin II increases V(max) of its actin-dependent MgATPase activity about 5-fold under normal assay conditions. Under these assay conditions, unphosphorylated chimeric myosins in which the tail domain of the Dictyostelium myosin II heavy chain is replaced by either the tail domain of chicken gizzard smooth muscle or Acanthamoeba myosin II are 20 times more active because of a 10- to 15-fold increase in V(max) and a 2- to 7-fold decrease in apparent K(ATPase) and are only slightly activated by regulatory light chain phosphorylation. Actin-dependent MgATPase activity of the Dictyostelium/Acanthamoeba chimera is not affected by phosphorylation of serine residues in the tail whose phosphorylation completely inactivates wild-type Acanthamoeba myosin II. These results indicate that the actin-dependent MgATPase activity of these myosins involves specific, tightly coupled, interactions between head and tail domains.